Hot ambient conditions do not alter intermittent cycling sprint performance - Almudehki, F.; Girard, O.; Grantham, J.; Racinais, S. (Journal of Science and Medicine in Sport, 2012)
Objectives: To investigate the effect of hot exposure on the ability to perform intermittent cycling sprints. Design: Repeated measures. Methods: Ten male volunteers performed 35 min of intermittent cycling comprising of 8 maximal 6-s sprints interspersed by 1 min of passive recovery followed by 4 min of constant-load pedaling (1W kg.1 of body weight) on a cycle ergometer in control (24.C, 24% rH) and hot (40.C, 40% rH) environments. Peak power output did not decrease during the exercise and was not dependent on the environmental temperature (average of 767 ± 120 W in control and 767 ± 119 W in hot, NS). Skin temperatures (e.g., chest: 36.8 ± 0.8 vs. 32.7 ± 0.6°C), heart rate (132 ± 13 vs. 118 ± 13 bpm) and rating of perceived exertion (13 ± 3 vs. 11 ± 3) were higher (all p < .05) in hot than control environment. However, EMG activity (RMS, vastus lateralis) and neuromuscular efficiency (power/RMS ratio) were similar at the two environmental conditions. Conclusions: Despite higher cardiovascular and perceptual strain in the hot trial, heat exposure did not alter neither peak power output nor related muscle activation and neuromuscular efficiency in the absence of hyperthermia (average core temperature of 37.6 ± 0.3°C in control vs. 37.7 ± 0.4°C in hot, NS).